Implementasi Habituasi dalam Pembinaan Profil Pelajar Pancasila pada Dimensi Gotong Royong Siswa Kelas 5 SD Negeri Ngaliyan 05. - Najwa Fauzia, Inha Wafda; Andriani, Aldina Eka; Adinesa, Azhara Eka; Musyarofah, Lailatul Eka; Istawa, Tasya Muhaima; Sidiq, Syahrir Muhaima (Jurnal Ilmiah Wahana Pendidikan, 2025)
The objective of this study is to describe the implementation of habituation in strengthening the character of fifth-grade students at SD Negeri Ngaliyan 05 through the aspect of mutual cooperation (gotong royong) in the Pancasila Student Profile. This research employs a descriptive qualitative approach and collects data through observation, interviews, and documentation. The findings indicate that habituation is implemented through routine programs such as Clean and Healthy Fridays, classroom duty schedules, student patrols, and waste donation (sodaqoh sampah). These activities have proven effective in instilling values of cooperation, responsibility, social awareness, and empathy among students. Minor challenges, such as jealousy among students, can be minimized through teacher role-modeling and intensive communication with parents. In conclusion, habituation is an ideal strategy for developing the character of mutual cooperation in students and can serve as a model for other primary schools in supporting the sustainable implementation of Pancasila values.